PENGARUH POS DAN BUDAYA ORGANISASI TERHADAP OCB DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - ASMARA, I MADE BOBI (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to analyze the influence of perceived organizational support and organizational culture on organizational citizenship behavior with organizational commitment as an intervening variable (case study at LPK Monarch Bali Dalung). The population of this study were all employees of LPK Monarch Bali Dalung. Respondents were determined using the saturated sample method, where the entire population was used as a sample, namely 44 people. The research analysis technique is to test the research hypothesis using `path analysis. The results of the analysis show that perceived organizational support and organizational culture influence organizational commitment and organizational citizenship behavior. Organizational commitment influences organizational citizenship behavior. The results of other research found that organizational commitment can act as an intervening variable on the influence of perceived organizational support on organizational citizenship behavior. Organizational commitment has not been able to act as an intervening variable in the influence of organizational culture on organizational citizenship behavior. The suggestions from this research are that it is hoped that the management of LPK Monarch Bali Dalung can increase perceived organizational support, organizational commitment, organizational culture in an effort to increase organizational citizenship behavior